Artificial intelligence in strategic business management: The case of auditing - Pereira, L.; Resio, M.; Lopes da Costa, R.; Dias, Á.; Gonçalves, R. (International Journal of Business Information Systems, 2024)
We live in the era of digital transformation and adopting innovative tools and technologies such as artificial intelligence (AI) seems to be extolling business models and driving optimisation in the processes inherent to their operation. The audit area which is intense in tasks that can be performed by machines, studies emerge showing positive results in the adoption of AI tools. The literature affirms the use of machinery such as AI in business models opens doors to the creation of value in organisations adjacent to this strategy. In order to deepen this contradictory approach between the benefits associated with the adoption of AI and the low rate of use of it, around 200 employees from mostly Portuguese companies were inquired. The research findings allow to understand what kind of work can be transferred for AI automatisation and present a list of technological issues to solve in this transformation.